Research progress on rehabilitation of language function in children with cerebral palsy under the organization and family rehabilitation model (脑瘫患儿机构结合家庭康复模式下语言功能康复的研究进展) - JIANG Muhe (蒋沐禾); WANG Yanbo (王艳波) (中西医结合护理)
This paper reviewed the rehabilitation of language function in children with cerebral palsy under the institutionalized and family rehabilitation mode, in order to provide reference for the rehabilitation training of language function in children with cerebral palsy in China. (本文对脑瘫患儿机构结合家庭康复模式下语言功能康复进行综述, 以期为我国脑瘫患儿语言功能康复训练提供参考与借鉴。)